In situ studies of biomineral deposition in the radula teeth of chitons of the suborder Chitonina - Brooker, L.; Lee, Alasdair; Macey, D.; Webb, J.; Van Bronswijk, Wilhelm (The Malacological Society of Japan, 2006)
The major lateral radula teeth of chitons (Mollusca: Polyplacophora) are composite materials, incorporating a variety of biominerals within an organic scaffold. While magnetite is ubiquitous to these teeth in all Polyplacophorans whose radulae have been described to date, this is not the case for the biominerals of the tooth core. In situ analsysis, using energy dispersive spectroscopy, to determine the distribution of elements in chiton teeth, and Raman spectroscopy, to identify the biominerals present, has been undertaken in the mature teeth of seven chiton species representing three families in the suborder Chitonina. The results show the tooth core to be comprised of a variety of elements, with the main biominerals identified as limonite, lepidocrocite and hydroxyapatite. Along with Ischnochiton australis, all five representatives of the Chitonidae deposit an apatitic mineral in their tooth core, while Plaxiphora albida does not deposit any calcium biomineral. With the exception of Acanthopleura chinata, the hydrated iron (III) oxide, limonite, is found in all species, including I. australis, which has relatively small amounts of iron in its tooth core. The lack of any evidence for a phosphate mineral in species that possess high levels of phosphorus in their core, challenges the long accepted notion that the presence of phosphorus implies its deposition as a biomineral. The combined techniques of energy dispersive spectroscopy and Raman spectroscopy provide a simple and effective means to evaluate, in situ, the biomineralisation strategies employed by chitons.While the results from this study are inconclusive in determining whether biomineralisation strategies reflect phylogenetic affinities in chitons, an extension of the study to include a wider range of chiton taxa could provide a basis for the utilisation of radula tooth biomineralisation as a systematic tool in this class of molluscs.